2021
DOI: 10.1088/1755-1315/735/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Mineralogical Nature of The Sediments of Sawa Lake in Muthanna Governorate, Southwestern Iraq

Abstract: The sediments of the Sawa lake surrounded area, southern Iraq, have unique proprieties that are interesting to researchers. Four sites located at varying distances from the lake were selected to study some of the properties of the lake sediment. The results indicate that the study soil is saline soils because of the values of the three salinity criteria (EC, TDS, and NaCl(. The values of electrical conductivity ranged between (100.11 and 74.78) ds.m−1for surface depths, whereas for subsurface depths ranged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…S5 + R1 produced the highest significant rise in the average final yield of 9.767 mg/ha compared to the control treatment of 3.380 mg/ha. This is because the organic fertilizer has an impact on increasing the efficiency of the bio-inoculum represented by increasing the numbers and activity of bacteria, and then increasing the availability of the nutrients, especially nitrogen, and increasing the solubility of some elements and making them readily available for absorption by the plant, thus increasing the yield [21,22,23]. As a result, the treatment (R1 + S5 + U75) recorded the highest average in the early yield of 10.982 mg/ha, but the control treatment recorded the lowest average of 2.018 mg/ha.…”
Section: Total Yieldmentioning
confidence: 99%
“…S5 + R1 produced the highest significant rise in the average final yield of 9.767 mg/ha compared to the control treatment of 3.380 mg/ha. This is because the organic fertilizer has an impact on increasing the efficiency of the bio-inoculum represented by increasing the numbers and activity of bacteria, and then increasing the availability of the nutrients, especially nitrogen, and increasing the solubility of some elements and making them readily available for absorption by the plant, thus increasing the yield [21,22,23]. As a result, the treatment (R1 + S5 + U75) recorded the highest average in the early yield of 10.982 mg/ha, but the control treatment recorded the lowest average of 2.018 mg/ha.…”
Section: Total Yieldmentioning
confidence: 99%
“…The organic fertilizer led to the availability of nutrients and organic materials needed by microorganisms. It raised the soil content of organic matter, thus increasing the activity of rhizobia bacteria, which leads to an increase in the number of bacterial nodules [12,13]. As a result, the triple inside (R1S5U75) produced the highest plant height of 72.841 cm/plant compared to the control treatment of 60.133. their numbers in the soil, which can infect roots and form knots, consistent with studies by [6,7].…”
Section: Number Of Bacterial Nodules (Knot/plant)mentioning
confidence: 99%
“…The results indicated that the bilateral interaction between G. mosseae and T. harzianum made the highest significant increase in the average phosphorous content in the plant, 0.416%, compared to the control treatment of 0.268%. The reason is due to the interference role of the two organisms in secreting growth-promoting substances and the role of VAM fungi in increasing the readiness and uptake of phosphorous and its transfer to the plant [23,24]. The triple interaction between the fungus (G.mosseae and T. harzianum) and the phosphate rock made the highest significant increase in the phosphorous content in the plant, 0.437%, compared to the control treatment of 0.240%.…”
Section: The Phosphorous Content In Plants (%)mentioning
confidence: 99%
“…4) presents the significant effect of applying G.mosseae on the average plant potassium content of 2.476% compared to the control treatment of 2.185%. The reason is attributed to the role of the fungus in Glomus mossea in increasing the solubility and absorption of nutrients, including potassium [23,24]. The application of T. harzianum gave a significant increase in the average plant potassium content of 2.405% compared to the control treatment of 2.257%.…”
Section: The Phosphorous Content In Plants (%)mentioning
confidence: 99%